Germline Variants in the POT1-Gene in High-Risk Melanoma Patients in Austria. Issue 5 (1st May 2018) - Müller, Christoph; Krunic, Milica; Wendt, Judith; von Haeseler, Arndt; Okamoto, Ichiro
Abstract: Risk of melanoma is in part determined by genetic factors. Currently the only established high penetrance familial melanoma genes are CDKN2A and CDK4. Recent studies reported germline variants in POT1 in melanoma families. In the present study, we sequenced the entire POT1 gene in 694 patients from the M3-study. Patients with multiple primary melanomas (n = 163) or with a positive family history (n = 133) were classified as high-risk melanoma patients. Additionally, 200 single primary melanoma patients and 198 non-melanoma controls were sequenced. For prediction analysis 10 different tools were used. In total 53 different variants were found, of which 8 were detected in high-risk melanoma patients, only. Two out of these 8 variants were located in exons and were non-synonymous: g.124510982 G>A (p.R80C) and g.124491977 T>G (p.N300H). While g.124491977 T>G was predicted to be neutral, 80% of the prediction tools classified g.124510982 G>A as deleterious. The variant, g.124467236 T>C, which possibly causes a change in the splice site was identified in a case with a positive family history in the present study. Another variant in the 5-UTR, g.124537261 A>G, was found in 2 high-risk patients. So, in conclusion, melanoma associated POT1 germline variants seem to be rare. Further studies are required to evaluate the role of POT1 for genetic counseling.